The Role of Schools, Parental Responsibilities, and Legal Implications for Bullying in Indonesia - Kalijunjung Hasibuan; Rizana Rizana (Eastasouth Institute, 2023)
Bullying is still a major problem that affects students' academic achievement and general well-being throughout the world. This study explores the functions of schools, parental responsibility, and legislative frameworks in addressing and preventing bullying within the particular setting of junior high schools in Indonesia. The study evaluates the frequency and forms of bullying, the efficacy of school-based interventions, the influence of parental engagement, and the advantages and disadvantages of the legal framework using a mixed-methods approach that includes surveys and interviews. According to quantitative research, bullying is occurring at alarming rates, with verbal bullying being the most common type. Although schools have anti-bullying policies in place, their execution might use some work. The important role that parents play is highlighted by positive correlations between lower incidence of bullying and parental involvement. Parents, teachers, and school administrators' qualitative observations offer a comprehensive perspective of the potential and obstacles in combating bullying. Evidence-based recommendations, such as strengthening school-based treatments, raising parental involvement, and improving the legislative framework, are informed by the integration of quantitative and qualitative findings. This study adds to the current conversation about bullying by offering perspectives specific to the Indonesian setting.